2017
DOI: 10.1080/14772019.2017.1412362
|View full text |Cite
|
Sign up to set email alerts
|

Identification of fossil worm tubes from Phanerozoic hydrothermal vents and cold seeps

Abstract: One of the main limitations to understanding the evolutionary history of hydrothermal vent and cold seep communities is the identification of tube fossils from ancient deposits. Tube-dwelling annelids are some of the most conspicuous inhabitants of modern vent and seep ecosystems, and ancient vent and seep tubular fossils are usually considered to have been made by annelids. However, the taxonomic affinities of many tube fossils from vents and seeps are contentious, or have remained largely undetermined due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 93 publications
0
29
0
1
Order By: Relevance
“…5), contrary to recent analyses that indicated that Jurassic tubes from Figueroa deposits were likely to have been made by vestimentiferans [46]. This adds to the growing evidence that the Cenozoic was a key period for the radiation of most dominant invertebrate taxa now occupying in deep-sea chemosynthetic communities [46, 47]. By comparison, the common siboglinid ancestor dates as far back as the Permian (267 mya ± 70).…”
Section: Resultsmentioning
confidence: 83%
“…5), contrary to recent analyses that indicated that Jurassic tubes from Figueroa deposits were likely to have been made by vestimentiferans [46]. This adds to the growing evidence that the Cenozoic was a key period for the radiation of most dominant invertebrate taxa now occupying in deep-sea chemosynthetic communities [46, 47]. By comparison, the common siboglinid ancestor dates as far back as the Permian (267 mya ± 70).…”
Section: Resultsmentioning
confidence: 83%
“…The suggestion that modern-day serpulids might be endemic to chemosynthetic habitats was proposed early on by other researchers (7,18), calling into question the assumption of obligate suspension feeding (14). By contrast, annelids within Sabellidae inhabit soft mucous and sediment tubes and thus leave only a minor fossil record (19).…”
Section: Introductionmentioning
confidence: 99%
“…The tube walls are now formed either of framboidal or colloform pyrite, and also retain fine details of the external tube wall ornamentation. Eoalvinellodes annulatus tubes often have thick walls comprising colloform pyrite that is many layers thick, and have external ornament of transverse, bifurcating wrinkles [ 18 , 20 , 25 ]. Small holes in E. annulatus tube walls have been interpreted as moulds of microorganisms [ 18 ].…”
Section: Introductionmentioning
confidence: 99%